Means of financing and financial analysis in industrial project evaluation - Darzi, Mushtaq A. (2000)
Before providing financial assistance, banks make a thorough evaluation of an industrial project in terms of its technical feasibility, commercial viability and financial soundness in order to ensure the repayments. For ascertaining financial soundness, various aspects studied are in relation to cost of project, means of financing, financial projections and financial analysis. The present study attempts to assess the approach of credit officers of commercial banks towards determination of means of financing and the usefulness of various techniques used in financial analysis in the evaluation of industrial projects. - Reproduced
Keywords: Production engineering; Project evaluation